PEMANFAATAN CARBOXY METHYL CELLULOSE DAN PATI SINGKONG SEBAGAI SUSPENDING AGENT PADA SEDIAAN SUSPENSI DAUN PANDAN - Rosaria Ika Pratiwi; Wilda Amananti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Pandan leaves have the effect of increasing the immune system so that it is necessary to develop the potential of pandan leaves as a medicinal preparation in the form of a suspension. The purpose of this study was to determine the secondary metabolites contained in pandan leaves and the best suspension formula in terms of the physical properties of the pandan leaf juice suspension (Pandanus amaryllifolius Roxb.). Three formulas for the suspension of Pandan leaf juice were made, the formula I used CMC suspending agent, formula II used cassava starch, formula III used CMC: cassava starch then carried out a physical test for the suspension of Pandan leaf juice including organoleptic test, pH, specific gravity, viscosity, and sedimentation. The next step is to determine the best formula in terms of the physical properties of the pandan leaf juice suspension. The secondary metabolites contained in pandan leaves through qualitative tests are flavonoids, alkaloids, saponins, tannins, and terpenoids. Formula I have a pH of 7, a specific gravity of 1.043, a viscosity of 20.57, and a sedimentation volume of 0, formula II has a pH of 7, a specific gravity of 1.049, a viscosity of 10.58, and a sedimentation volume of 0.75, while formula III has a pH of 8, specific gravity 1.053, viscosity 26.27, and sedimentation volume 0.975. The best formula in terms of the physical properties of the pandan leaf juice suspension (Pandanus amaryllifolius Roxb.) Is formula I with Carboxy Methyl Cellulose (CMC) as a suspending agent.